2022
DOI: 10.1108/jes-06-2022-0348
|View full text |Cite
|
Sign up to set email alerts
|

Government failures and non-performing loans in Asian countries

Abstract: PurposeNon-performing loans (NPLs) may determine an overall weakness of the banking system within a country. The purpose of the present study is to analyze the impact of government failures on NPLs in Asian countries in the time span 2000–2020. The variables employed as proxies of government failures are public debt as % of gross domestic product (GDP) and a government ineffectiveness index proposed by the World Bank.Design/methodology/approachThe econometric approach employed is a panel generalised time serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Finally, the FDI is positively related to the CNPL rises in the FDI will increase the CNPL by .4821061. This is supported by Giammanco et al (2022), arguing that increases in FDI encourage banks to relax their credit terms to issue more loans to foreign businesses, which consequently raises the CNPL. On the other side, the RNPL results have revealed that the CAR is statistically significant and positively associated with the RNPL, while LTD is negatively related to it.…”
Section: The Results Of Gmm and Discussionmentioning
confidence: 95%
“…Finally, the FDI is positively related to the CNPL rises in the FDI will increase the CNPL by .4821061. This is supported by Giammanco et al (2022), arguing that increases in FDI encourage banks to relax their credit terms to issue more loans to foreign businesses, which consequently raises the CNPL. On the other side, the RNPL results have revealed that the CAR is statistically significant and positively associated with the RNPL, while LTD is negatively related to it.…”
Section: The Results Of Gmm and Discussionmentioning
confidence: 95%
“…The non-performing financing (NPF) ratio reflects a measure of the stability of an Islamic bank. Banks must keep non-performing loans or financing to a minimum (Kuzucu & Kuzucu, 2019) to create a stable banking system (Giammanco et al, 2022). The NPL ratio at conventional banks measures credit risk, including non-performing financing and provisions to evaluate the banking sector's stability, fragility and long-term financial sustainability (Ashikuzzaman, 2022).…”
Section: Variablesmentioning
confidence: 99%
“…While recent studies on NPLs abound (Bayar 2019;Ozili 2019;Khan et al 2020;Misman and Bhatti 2020;Fallanca et al 2021;Karadima and Louri 2021;Phung et al 2022;Golitsis et al 2022;Fakhrunnas et al 2022;Hakimi et al 2022;El-Chaarani and Abraham 2022;Foglia 2022;Erdas and Ezanoglu 2022;Alnabulsi et al 2022;Jubilee et al 2022;Mdaghri 2022;Giammanco et al 2022;Apergis 2022;Akhter 2023), they mainly examine the banking sector of developed, large, and developing and emerging economies. Notably, just a few studies have focused on small island countries (Kumar et al 2018;Chand et al 2021), and these are generally restrictive in terms of the model specification, sample, and scope.…”
Section: Introductionmentioning
confidence: 99%